The story behind coal - A Somervill, Barbara (Chicago, IL Heinemann Library, 2012)
Explains what coal is, what its uses are, how it is obtained, and the environmental challenges it causes
A gift from book Africa
Enviroment
1 2 13 15
Keywords: Coal; JUVENILE NONFICTION -- Social Issues -- General (see also headings under Family)